Carnival of the animals [compact disc] - Morpurgo, Michael (Decca, 2020)
The musical Kanneh-Mason family joins Oscar-winning actress Olivia Colman and beloved author Michael Morpurgo for an album of magical storytelling this holiday season. Carnival features a performance of Saint-Saens' beloved Carnival Of The Animals Suite. New poems by Morpurgo, plus narration from Morpurgo/Colman. Interspersed with classics like "Flight of the Bumble Bee" and "Dance of the Sugar Plum Fairy." The siblings close the album together with an arrangement of Marley's "Redemption Song."